Galaxy and Mass Assembly (GAMA): luminosity function evolution. Issue Volume 10:Issue S306(2014) (1st July 2015) - Loveday, Jon; ,
Abstract: We describe modifications to the joint stepwise maximum likelihood method of Cole (2011) in order to simultaneously fit the GAMA-II galaxy luminosity function (LF), corrected for radial density variations, and its evolution with redshift. The whole sample is reasonably well-fit with luminosity ( Q ) and density ( P ) evolution parameters Q, P ≈ 0.8, 1.7. Red galaxies show larger luminosity but smaller density evolution than blue galaxies, as expected.